Warfare to Welfare: How Social Identity Supports the Political Business of the Former Free Aceh Movement - Hajad, Vellayati; Aprita Sari, Cut Maya (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
This study critically examines how former members of the Free Aceh Movement (GAM) transformed their collective social identity into political and economic capital in post-conflict Aceh. Drawing on social identity theory (SIT) and sociocognitive processes, it challenges prevailing reintegration narratives that emphasise disassociation from militant pasts. Instead, it finds that former GAM members deliberately retained and mobilised their rebel identity to gain legitimacy, patronage, and access to state resources. The study identifies three internal identity trajectories: the “ruling group